2021
DOI: 10.3389/fmed.2021.708717
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Blepharophimosis and Ptosis as Leading Dysmorphic Features of Rare Congenital Malformation Syndrome With Developmental Delay – New Cases With TRAF7 Variants

Abstract: Germline variants in tumor necrosis factor receptor-associated factor 7 (TRAF7) gene have recently been described in about 50 patients with developmental delay and cardiac, facial, and digital anomalies (CAFDADD). We aimed to depict further the clinical and genetic spectrum associated with TRAF7 germline variants in two additional patients, broaden the mutational spectrum, and support the characteristic clinical variety to facilitate the diagnostics of the syndrome among physician involved in the evaluation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Bouwmeester et al (2004) found that homodimerization of TRAF7 occurs at the central TRAF and CC domains whereas its WD40 repeats bind MEKK3, a mouse homolog for mitogen‐activated protein kinase kinase kinase 3 (MAP3K3). Notably, most somatic and germline variants are identified in this WD40 domain (Castilla‐Vallmanya et al, 2020; Paprocka et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Bouwmeester et al (2004) found that homodimerization of TRAF7 occurs at the central TRAF and CC domains whereas its WD40 repeats bind MEKK3, a mouse homolog for mitogen‐activated protein kinase kinase kinase 3 (MAP3K3). Notably, most somatic and germline variants are identified in this WD40 domain (Castilla‐Vallmanya et al, 2020; Paprocka et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The phenotypic spectrum of this condition can include congenital heart defects, digital abnormalities, dysmorphic facial features, micro and macrocephaly, renal anomalies, intellectual disability, seizures, and hearing loss. 2,3 All previous reports of affected individuals are children and adults. To our knowledge, a prenatal diagnosis of this condition has not yet been reported.…”
mentioning
confidence: 99%
“…All variants were confirmed to have occurred de novo , except for P1, conceived by ovodonation, for whom the paternal sample was negative. Eight different variants have been detected (Table 3), seven of them previously associated with TRAF7 syndrome [1,2,5,7] including the recurrent variant p.Arg655Gln, which was detected in four unrelated patients (Patients 8 to 11). Patient 7 harbors a novel variant, c.1958G>T, p.(Arg653Leu), in a residue where other amino acid substitutions have been previously reported in meningiomas [25].…”
Section: Resultsmentioning
confidence: 99%
“…This apparent division where some missense changes in germline lead to TRAF7 patients migth be due to a correlation in the pathomechanisms of both RASopathies and TRAF7 syndrome involving the regulation of RAS/MAPK signaling pathways [1,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation